Robotic versus laparoscopic total mesorectal excision with lateral lymph node dissection for advanced rectal cancer: a systematic review and meta-analysis - Chaouch, Mohamed Ali; Hussain, Mohammad Iqbal; Costa, Adriano Carneiro da; Mazzotta, Alessandro; Krimi, Bassem; Gouader, Amine; Cotte, Eddy; Khan, Jim; Oweira, Hani (PLOS ONE, 2024)
Introduction Lateral pelvic node dissection (LPND) poses significant technical challenges. Despite the advent of robotic surgery, determining the optimal minimally invasive approach remains a topic of debate. This study aimed to compare postoperative outcomes between robotic total mesorectal excision with LPND (R-LPND) and laparoscopic total mesorectal excision with LPND (L-LPND). Methods This meta-analysis was conducted according to the Preferred Reporting Items for Systematic Review and Meta-analysis (PRISMA) 2020 and AMSTAR 2 (Assessing the Methodological Quality of Systematic Reviews) guidelines. Utilizing the RevMan 5.3.5 statistical package from the Cochrane Collaboration, a random-effects model was employed. Results Six eligible studies involving 652 patients (316 and 336 in the R-LPND and L-LPND groups, respectively) were retrieved. The robotic approach demonstrated favourable outcomes compared with the laparoscopic approach, manifesting in lower morbidity rates, reduced urinary complications, shorter hospital stays, and a higher number of harvested lateral pelvic lymph nodes. However, longer operative time was associated with the robotic approach. No significant differences were observed between the two groups regarding major complications, anastomotic leak, intra-abdominal infection, neurological complications, LPND time, overall recurrence, and local recurrence. Conclusions In summary, the robotic approach is a safe and feasible alternative for Total Mesorectal Excision (TME) with LPND in advanced rectal cancer. Notably, it is associated with lower morbidity, particularly a reduction in urinary complications, a shorter hospital stay and increased number of harvested lateral pelvic nodes. The trade-off for these benefits is a longer operative time.
Gesehen am 19.12.2024